Systems thinking based approaches to engage with health inequities shaping Antimicrobial Resistance in low and lower-middle-income countries - Arunima S. Mukherjee; Sundeep Sahay (Journal of Infection and Public Health, 2023)
This paper argues for ‘systems thinking’ as a conceptual framework to address antimicrobial resistance, especially focusing on the context of low and lower middle-income countries (LLMICs), which are plagued with health inequities that magnify the AMR threat. Systems thinking provides two avenues to enhance these mitigation efforts: i) it helps go beyond a purely biomedical approach to incorporate considerations of the social and informational; ii) particularly relevant as is it helps to understand the role of health inequities in shaping AMR related prevention and care processes.